Didactics of history and historical consciousness: the problem of interrelation - Arūnas Poviliūnas (Lietuvos Istorijos Studijos)
The paper discusses the general principles of compatibility between history and social science studies. Modernity has transformed the ancient belief that historia est magistra vitae (Cicero) and one common discourse of history has split into two different parts: academic history and didactics of history. This division has fostered the development of scientific history but, on the other hand, the gap between academic history and historical teaching has increased.